2017
DOI: 10.1007/s00709-017-1198-5
|View full text |Cite
|
Sign up to set email alerts
|

Localization and subcellular association of Grapevine Pinot Gris Virus in grapevine leaf tissues

Abstract: Despite the increasing impact of Grapevine Pinot gris disease (GPG-disease) worldwide, etiology about this disorder is still uncertain. The presence of the putative causal agent, the Grapevine Pinot Gris Virus (GPGV), has been reported in symptomatic grapevines (presenting stunting, chlorotic mottling, and leaf deformation) as well as in symptom-free plants. Moreover, information on virus localization in grapevine tissues and virus-plant interactions at the cytological level is missing at all. Ultrastructural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 54 publications
1
24
0
Order By: Relevance
“…In fact, GPGV−/+B and GPGV+/+B plants displayed well-preserved root cells with normal histological and ultrastructural organization (Figures 2A-H, respectively). GPGV, detected in the BSCs of roots of GPGV+/+B plants, was not associated with any alteration besides membrane-bound organelle, described by Tarquini et al (2018) as putative endoplasmic reticulum (ER) rearrangement ( Figure 2F; Tarquini et al, 2018). In the case of B starvation, GPGV− root tissues displayed strong perturbation of both cortical and vascular regions ( Figure 2I).…”
Section: Microscopy Observationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, GPGV−/+B and GPGV+/+B plants displayed well-preserved root cells with normal histological and ultrastructural organization (Figures 2A-H, respectively). GPGV, detected in the BSCs of roots of GPGV+/+B plants, was not associated with any alteration besides membrane-bound organelle, described by Tarquini et al (2018) as putative endoplasmic reticulum (ER) rearrangement ( Figure 2F; Tarquini et al, 2018). In the case of B starvation, GPGV− root tissues displayed strong perturbation of both cortical and vascular regions ( Figure 2I).…”
Section: Microscopy Observationsmentioning
confidence: 99%
“…Cuttings were obtained from dormant canes of grapevines (cv Pinot gris, clone VCR 5), collected in December 2017 from symptomatic and asymptomatic plants of a 12-yearold vineyard located in Farra d'Isonzo (Gorizia Province, Italy;45.91676765918134 N, 13.530162621173078 E). The eventual occurrence of the main grapevine viruses (Giampetruzzi et al, 2012;Saldarelli et al, 2015;Bertazzon et al, 2017;Gentili et al, 2017;Morán et al, 2018;Tarquini et al, 2018;Marra et al, 2019;Tarquini et al, 2019a,b) was checked as described in Tarquini et al (2018) and Tarquini et al (2019a). The presence of viruses included in the Italian certification program (Bertazzon et al, 2002) was excluded, while the detection of viruses and viroids reported in Pinot gris tissues simultaneously with GPGV (Giampetruzzi et al, 2012 andSaldarelli et al, 2015, i.e.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations